n → ∞ lim e 2 1 × e 4 1 × e 6 1 × … × e 2 n 1 e × e 3 1 × e 5 1 × e 7 1 × … × e 2 n + 1 1 = ?
Try this one
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple but very nice solution :D
oh yea I forgot about the expansion of Ln(1+x). I tried multiplying by the product on the denominator to give: n → ∞ lim k = 1 ∏ n e k 1 k = 1 ∏ 2 n + 1 e k 1 = n → ∞ lim k = n + 1 ∏ 2 n e k 1 = e u w h e r e u = n → ∞ lim k = 1 ∑ n n + k 1 = n + 1 1 + n + 2 1 + . . . + 2 n 1 But I couldn't figure out the last step. Do you know how I could show that n → ∞ lim k = 1 ∑ n n + k 1 = L n 2 ?
Log in to reply
That's equal to H 2 n − H n , where H n = 1 + 2 1 + ⋯ + n 1 . Since H n ≈ ln n + γ , we have lim n → ∞ ( H 2 n − H n ) = lim n → ∞ ( ( ln 2 n + γ ) − ( ln n + γ ) ) = lim n → ∞ ( ln 2 n − ln n ) = ln 2 .
Or, alternatively, you can show that ∑ k = 1 n n + k 1 = 1 − 2 1 + ⋯ − 2 n 1 , and use the series for ln 2 . (Hint: Show that they're both equal to H 2 n − H n .)
Or, even more alternatively, use the ideas used in my answer, using the squeeze theorem.
Tanishq Varshney has given the "obvious" solution. I'll add another one. This one uses no infinite series, no integrals, no derivatives. In fact, the only "calculus-y" thing is the squeeze theorem at the very end!
Multiplying top and bottom by e 2 1 × ⋯ × e 2 n 1 and rearranging, we find that this is equal to: n → ∞ lim e n + 1 1 + n + 2 1 + n + 3 1 + ⋯ + 2 n + 1 1 Now, recall that e x ≥ x + 1 for all x . ( Helpful graph )
Letting x = n + 1 1 , n + 2 1 , etc., and multiplying them together, we get the following: e n + 1 1 + ⋯ + 2 n + 1 1 ≥ n + 1 n + 2 × n + 2 n + 3 × ⋯ × 2 n + 1 2 n + 2 = n + 1 2 n + 2 = 2 Thus, we get a lower bound of 2 . In addition, take e x ≥ x + 1 again, and let x = − n + 1 1 , − n + 2 1 , etc. This gives:
e − n + 1 1 − ⋯ − 2 n + 1 1 ≥ n + 1 n × n + 2 n + 1 × ⋯ × 2 n + 1 2 n = 2 n + 1 n
Taking the reciprocal: e n + 1 1 + ⋯ + 2 n + 1 1 ≤ n 2 n + 1 = 2 + n 1
So, we now have: 2 ≤ e n + 1 1 + ⋯ + 2 n + 1 1 ≤ 2 + n 1 The squeeze theorem tells us that the limit is 2 .
Problem Loading...
Note Loading...
Set Loading...
e 1 − 2 1 + 3 1 − 4 1 + 5 1 . . .
l n ( 1 + x ) = x − 2 x 2 + 3 x 3 − . . . .
put x = 1
e l n 2
2